Fingertip replantation: Technical considerations and outcome analysis of 24 consecutive fingertip replantations - H Venkatramani; S Raja Sabapathy (Indian Journal of Plastic Surgery)
Fingertip amputations are one of the most common injuries faced in an emergency department. Finger tip replantation though technically possible, are not regularly done due to the presumed complexity of the procedure and doubts about the outcome. This article deals with our experience of 24 fingertip replantations in 24 patients done over a period of 8 years since the year 2000. Twenty-one fingertips survived. The most common affected digit in the series was thumb followed by index, middle, and ring. The overall success rate was 87%. Both arterial and venous repair were done in all cases. Replantation was not done if no suitable vein was found for anastomosis. Nine patients did not have nerve repair. Seven of them survived and all of them had satisfactory sensation when examined after 1 year. No patient suffered from cold intolerance. All patients were satisfied with the functional outcome and aesthetic appearance. This article highlights the technical considerations and the outcome of these fingertip replants.